THEORETICAL AND METHODOLOGICAL BASES FOR EVALUATING THE EFFECTIVENESS OF IMPLEMENTATION STRATEGIES OF THE DIVIDEND POLICY OF CORPORATE AGRICULTURAL ENTERPRISES - SUSLIKOV, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
It has been shown that the dividend policy of a corporate agricultural enterprise is one of the determining factors in the formation of its investment attractiveness in the stock market and is implemented by the company in accordance with the strategy adopted by the top management. An algorithm for strategizing an effective dividend policy of corporate agricultural enterprises has been developed, which includes: analysis of the business environment and assessment of factors influencing the dividend policy of the enterprise; selection of the type of dividend policy; substantiation of the ratio of net profit distribution between reinvestment and dividend payments and selection of the dividend strategy; establishment of the dividend payout ratio and the amount of dividend per share; analysis and evaluation of the effectiveness of the corporate dividend policy and its adjustment. It is substantiated that evaluation of the efficiency of implementation of the dividend policy strategy of a corporate agricultural enterprise should be carried out from the standpoint of the riskiness of investing in the company’s shares and the stability of dividend payments during the period under study. A methodical approach to assessing the stability of dividend payments based on the theory of probability and the expert method has been developed. The proposed method includes estimates of the regularity of payments and the variability of the amount of dividend payments based on data on the amount of dividend per share. The efficiency of implementation of the dividend policy strategies of the leading corporate agricultural enterprises of Ukraine for 2010-2021 has been analyzed. It has been established that the main problems are irregularity of dividend payments, their high variability, riskiness of securities, as well as complete insecurity of the interests of minority shareholders, which has already formed a long-term negative image of agricultural companies, in particular on international stock exchanges. It has been shown that the institutional basis for an effective dividend strategy of corporate agricultural enterprises should be the development of the national stock market, transformation and adaptation of corporate governance models, as well as regulatory support for dividend policy.